Penerapan Media Gambar Dalam Pembelajaran Bahasa Arab Terhadap Penguasaan Kosakata Siswa Kelas VII MTs Negeri 3 Enrekang - Nurhidayah Masdi Siduppa; A. Fajriwati Tadjuddin; Sulaeman Masnan (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2021)
The purpose of this study is to find out the apllication of Image Media in Arabic Language Learning on vocabulary mastery of Grade VII Mts Negeri 3 Enrekang students. This study uses Class Action Research. Data collection techniques are observation techniques, tests, and documentation.The results showed an increase from cycle I to cycle II. From the test data, it can be known that the average grade score of 24 students in cycle I is 64,84, and in cycle II is 85,55. It is known that the increase was 11,20% from meeting I to the second meeting. And there was an increase of 62,70% from the second meeting to the third meeting followed by an increase of 34,70% from meeting III to meeting IV. Based on the research conducted, the results of the improvement of mastery of Arabic vocabulary through image media in grade VII students of Mts Negeri 3 Enrekang is 36,21% this indicates that the use of image media is effectively used in the mastery of Arabic vocabulary.